2010
DOI: 10.1007/978-3-642-13881-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Meronymy Relationships from Domain-Specific, Textual Corporate Databases

Abstract: Abstract.Various techniques for learning meronymy relationships from opendomain corpora exist. However, extracting meronymy relationships from domain-specific, textual corporate databases has been overlooked, despite numerous application opportunities particularly in domains like product development and/or customer service. These domains also pose new scientific challenges, such as the absence of elaborate knowledge resources, compromising the performance of supervised meronymy-learning algorithms. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Broadly speaking, semantic relations are labeled relations between meanings, as well as between meanings and representations. In contrast to associations, semantic relations have meanings as Hyponymy-hypernymy Hearst 1992;Caraballo 1999;Kozareva et al 2008;Pantel and Ravichandran 2004;Pantel and Pennacchiotti 2006;Snow et al 2005;Navigli and Velardi 2010;Bordea et al 2015 Meronymy-holonymy Berland and Charniak 1999;Girju et al 2006;Ittoo et al 2010;Pantel and Pennacchiotti 2006 Causal relations Khoo et al 2000;Girju and Moldovan 2002;Blanco et al 2008;Ittoo and Bouma 2011 indicated by their labels. The number of semantic relations is virtually unlimited.…”
Section: Semantic Relationmentioning
confidence: 99%
“…Broadly speaking, semantic relations are labeled relations between meanings, as well as between meanings and representations. In contrast to associations, semantic relations have meanings as Hyponymy-hypernymy Hearst 1992;Caraballo 1999;Kozareva et al 2008;Pantel and Ravichandran 2004;Pantel and Pennacchiotti 2006;Snow et al 2005;Navigli and Velardi 2010;Bordea et al 2015 Meronymy-holonymy Berland and Charniak 1999;Girju et al 2006;Ittoo et al 2010;Pantel and Pennacchiotti 2006 Causal relations Khoo et al 2000;Girju and Moldovan 2002;Blanco et al 2008;Ittoo and Bouma 2011 indicated by their labels. The number of semantic relations is virtually unlimited.…”
Section: Semantic Relationmentioning
confidence: 99%
“…Ranked list of synonyms [21] Similar to finding synonyms, a number of algorithms have been proposed for identifying part-whole relationships. [25] presents an approach for finding part-whole relationships in domain-specific data. Part-whole relationships in domain-specific data is more difficult to address than such relationships in general language, as the available data is much smaller.…”
Section: [Tapez Ici]mentioning
confidence: 99%
“…As a consequence, it is more difficult to train machine learning algorithms. The approach proposed in [25] leverages on part-whole relationships extracted from an open-domain corpus and extends these relationships by domainspecific relationships. [26] is arguably the first automatic part extraction from a large, unlabeled, corpus with a reported precision of 0.55.…”
Section: [Tapez Ici]mentioning
confidence: 99%
“…Currently, some work studied ASR for Urdu [13][14][15][16][17][18][19][20]. Additionally, numerous works [12,17,[21][22][23] have been done on spoken digit recognition for Urdu.…”
Section: Introductionmentioning
confidence: 99%